Differential response of corals to regional mass‐warming events as evident from skeletal Sr/Ca and Mg/Ca ratios. (2nd May 2017) - Clarke, Harry; D'Olivo, Juan Pablo; Falter, James; Zinke, Jens; Lowe, Ryan; McCulloch, Malcolm
Abstract: During the summer of 2010/2011, a regional marine heat wave resulted in coral bleaching of variable severity along much of the western coastline of Australia. At Ningaloo Reef, a 300 km long fringing reef system and World Heritage site, highly contrasting coral bleaching was observed between two morphologically distinct nearshore reef communities located on either side of the Ningaloo Peninsula: Tantabiddi (∼20% bleaching) and Bundegi (∼90% bleaching). For this study, we collected coral cores ( Porites sp.) from Tantabiddi and Bundegi reef sites to assess the response of the Sr/Ca temperature proxy and Mg/Ca ratios to the variable levels of thermal stress imposed at these two sites during the 2010/2011 warming event. We found that there was an anomalous increase in Sr/Ca and decrease in Mg/Ca ratios in the Bundegi record that was coincident with the timing of severe coral bleaching at the site, while no significant changes were observed in the Tantabiddi record. We show that the change in the relationship of Sr/Ca and Mg/Ca ratios with temperature at Bundegi during the 2010/2011 event reflects changes in related coral "vital" processes during periods of environmental stress. These changes were found to be consistent with a reduction in active transport of Ca 2+ to the site of calcification leading to a reduction in calcification rates and reduced Rayleigh fractionation of incorporated trace elements. Plain Language Summary: In this paper, we compare coral‐core geochemical records (Sr/Ca and Mg/Ca) from two reef sites at Ningaloo Reef, Western Australia, which showed highly contrasting coral bleaching severities following a regional heat wave during the summer of 2010/11. We show that anomalous increases in Sr/Ca ratios and decreases in Mg/Ca ratios can provide a distinct signature of past thermal stress events making core records useful for understanding the variable impacts of regional ocean warming events within reef ecosystems. Furthermore, by using a novel approach we were able to explain the formation of these anomalies during periods of thermal stress through changes in coral physiological and kinetic processes, which, along with temperature, also effect the incorporation of trace elements in coral skeleton. This is of particular importance as coral core records are heavily relied upon for the understanding of climate change, yet the mechanisms responsible for acute changes in coral trace element ratios during periods of thermal stress have previously not been discussed. We thus hope our work will contribute to the understanding of coral physiology and the development of more robust records of climate change in the future. Key Points: Geochemical anomalies observed in coral core records indicate the significance of "vital" effects in paleoclimate reconstructions Anomalous increases and decreases in coral Sr/Ca and Mg/Ca ratios provide a distinct signature of past thermal stress events Sr/Ca and Mg/Ca anomalies can be explained by a decrease in active Ca 2+ transport and decreased Rayleigh Fractionation